2002
DOI: 10.1346/00098600260358111
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Displacement on Imogolite

Abstract: The adsorption of 13 C-labeled benzene on imogolite has been studied on samples which had been evacuated and then heated to remove water below their decomposition point. After adsorption of labeled benzene, the samples were studied by nuclear magnetic resonance using non-spinning techniques. The results show that benzene can occupy more than one pore type and that water does not displace benzene from the intra-tube pores at atmospheric pressure. A further finding is that there are at least two types of adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
(25 reference statements)
0
30
0
Order By: Relevance
“…Imogolites have adsorption properties of cations ͑Cd + , Cu + , Pd + ͒ 22 and ͑Ag + ͒, 23 neutral molecules like benzene, 24 water, 25 ammonia, 26 and possible applications in the energy storage-management of methane. 27 Additionally, the adsoption of chlorite by imogolites in a wide pH range 45 is wellknown, and it has been suggested the existence of a high point of zero charge in the outer parts of the imogolite, based on electrophoretic mobility studies.…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Imogolites have adsorption properties of cations ͑Cd + , Cu + , Pd + ͒ 22 and ͑Ag + ͒, 23 neutral molecules like benzene, 24 water, 25 ammonia, 26 and possible applications in the energy storage-management of methane. 27 Additionally, the adsoption of chlorite by imogolites in a wide pH range 45 is wellknown, and it has been suggested the existence of a high point of zero charge in the outer parts of the imogolite, based on electrophoretic mobility studies.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…17,21 Due to this surface area, together with the chemistry inherent to their surface, imogolites have been proposed as good metallic adsorbent of cations: ͑Cd + , Cu + , Pd + ͒, 22 ͑Ag + ͒, 23 and neutral molecules like benzene, 24 water, 25 and ammonia 26 with possible applications in the energy storage-management of methane. 27 In catalysis, imogolites have been investigated as a possible catalytic support of Cu and Pt particles.…”
Section: Introductionmentioning
confidence: 99%
“…This structure gives rise to three kinds of pores (Ackerman et al 1993;Wilson et al 2002) shown in Scheme 1: (i) pores A are intra-tube pores, 1.0 nm in diameter, lined by silanols, the related A surface being very hydrophilic and able to interact with probes like H 2 O, NH 3 and CO (Bonelli et al 2009;2013); (ii) pores B, 0.3-0.4 nm wide, are those among the three aligned NTs within a bundle, hardly accessible even to small molecules, like water (Ackerman et al 1993;Wilson et al 2002); (iii) pores C are disordered slit (meso)pores among bundles, the surface of which may interact with larger molecules, like phenol (Bonelli et al 2009) and 1,3,5-triethylbenzene (Bonelli et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Its stoichiometry is (OH) 3 AI 2 O 3 SiOH and it has at least two kinds of active surface sites, an internal one dominated by silanol groups (≡ Si-OH) and an external one dominated by aluminol groups (≡Al-OH) [8][9][10], both with pH-dependent surface charge. Because of the unique physicochemical characteristics of this IONt, various synthetic processes have been developed [9,[11][12][13][14][15], reinforcing its industrial applications.…”
Section: Introductionmentioning
confidence: 99%